2008
DOI: 10.1055/s-2007-1005941
|View full text |Cite
|
Sign up to set email alerts
|

Sonographische Darstellung von Lungenembolien. Ergebnisse einer prospektiven Studie

Abstract: 1. tentative diagnosis of pulmonary embolism by clinical signs (n = 47) 2. only chest pain in breathing (n = 32), 3. deep vein thrombosis without signs of pulmonary embolism (n = 21). In 67 cases perfusion lung scans ware available. The typical sonographic sign is a wedge-shaped echo-poor lesion with or without a local effusion. In the first group, both methods coincided positively in 28 cases, whereas only the scan detected pulmonary embolism in 6 cases. In the second group, 8 cases were found by ultrasound, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Despite the fact that using TUS for the diagnosis of pulmonary embolism was described >50 years ago, research in the area has primarily evolved within the past two decades, with several descriptive and diagnostic accuracy studies [15,29,[150][151][152][153][154][155][156][157][158][159][160][161][162][163][164]. In a meta-analysis of the diagnostic accuracy of TUS for pulmonary embolism, SQUIZZATO et al [165] reported a bivariate weighted mean sensitivity and specificity Air bronchograms (A) are present and can be seen as hyperechoic dots or lines within the consolidation.…”
Section: Lung Consolidation Overview Of the Evidence And Current Practicementioning
confidence: 99%
“…Despite the fact that using TUS for the diagnosis of pulmonary embolism was described >50 years ago, research in the area has primarily evolved within the past two decades, with several descriptive and diagnostic accuracy studies [15,29,[150][151][152][153][154][155][156][157][158][159][160][161][162][163][164]. In a meta-analysis of the diagnostic accuracy of TUS for pulmonary embolism, SQUIZZATO et al [165] reported a bivariate weighted mean sensitivity and specificity Air bronchograms (A) are present and can be seen as hyperechoic dots or lines within the consolidation.…”
Section: Lung Consolidation Overview Of the Evidence And Current Practicementioning
confidence: 99%
“…There were 5 studies published pre-2000 [1719, 31, 32], and the pooled sensitivity, specificity, PLR, NLR and DOR were 0.94 (95% CI, 0.89 to 0.96), 0.74 (95% CI, 0.61 to 0.85), 3.64 (95% CI, 2.26 to 5.84), 0.09 (95% CI, 0.05 to 0.16) and 42.31 (95% CI, 17.15 to 104.4). The HSROC was 0.95 (95% CI, 0.92 to 0.96).…”
Section: Resultsmentioning
confidence: 99%
“…Häufig gehen einer massiven Lungenembolie kleinere emboli− sche Ereignisse voraus, die dann als Signalembolien zur Darstel− lung kommen. Solche kleinen Läsionen können sowohl als Vor− boten eine drohende Lungenembolie signalisieren, aber auch bei einer massiven zentralen Lungenembolie gleichzeitig beste− hen und somit die Diagnose stützen, ohne dass der zentrale Em− bolus selbst thoraxsonographisch nachweisbar ist, was wegen der dazwischen liegenden Luft nicht gelingen kann [16,23]. Kontrastmittelsonographie: Lungeninfarkte und emboliebe− dingte Hämorrhagien zeigen in der Kontrastmittel unterstützten Sonographie, wie in der Farbdopplersonographie, eine fehlende Durchblutung bzw.…”
unclassified